Multi-scale investigation on the adhesion properties of warm-mixed recycled SBS modified asphalt. (9th May 2023) - Li, Bo; Li, Andi; Chen, Xiaowei; Nan, Xueli; Li, Zhiwei; Qiu, Ke; Ji, Haidong
Highlights: The multi-scale study was conducted on the adhesion properties of the WMRA. The effect of aged SBS modified asphalt content on the adhesion properties of the WMRA in macroscopic and microscopic scales was studied. The micromorphology and nano-adhesion of WMRA were studied with AFM technology. The pull-off strength of WMRA exhibited an excellent correlation with the adhesion roughness index Ra of WMRA. Abstract: The adhesion properties have been a major concern of warm mix recycled SBS modified asphalt. This study aims to evaluate the adhesion properties of warm mix recycled SBS modified asphalt on multi-scale. Three kinds of asphalt (blends of aged and unaged SBS modified asphalt [AUA], AUA with rejuvenator [ARA], and ARA with warm additive [WMRA]) were prepared. The effects of the content of aged SBS modified asphalt, rejuvenator and wax-based warm additive on the adhesion of WMRA were investigated using the pull-off test and surface free energy theory. The micromorphology and nano-adhesion were measured by atomic force microscopy (AFM), and the test data were compared with macroscopic adhesion. The results showed that the Lewis acid component of AUA increased with the raised content of aged SBS modified asphalt. The wax-based warm additive caused a decrease in the Lewis acid component, which caused the adhesion work of WMRA to be lower than that of AUA and ARA. When the content of aged SBS modified asphalt was low, the rejuvenator could improve the adhesion of AUA and reached a peak at 20%. After adding the wax-based warm additive, the microscopic surface of WMRA showed irregular and non-uniform morphological characteristics, and the bee structure was unclear and gathered to form an island-like structure. The crystallization of wax-based warm additive on the asphalt surface caused the increased of WMRA on nano-adhesion and roughness indexes. The adhesion work and adhesion roughness index Ra could be used to evaluate the adhesion of the WMRA.